Acetylcholinesterase Activity in Veterans of the First Gulf War. (1st November 2007) - Concato, John; Aslan, Mihaela; Palmisano, Margaret M.; Doebbeling, Caroline Carney; Peduzzi, Peter; Ofek, Keren; Soreq, Hermona; Doebbeling, Bradley
Abstract : Background: Factors affecting acetylcholine-mediated neurotransmission have been proposed as possible explanations for physical and mental health symptoms among veterans of the 1990-1991 Gulf War. This study was designed to examine relationships of deployment to the Gulf, as well as symptoms after military service, with postdeployment activity of acetylcholinesterase (AChE) and related enzymes. Methods: The patient population included 488 veterans, originally from Iowa at enlistment, who served in the US military during August 1990 to July 1991. Demographic, military, and clinical characteristics were obtained from a population-based cohort study (in 1995-1996) and from a nested case-control study (in 1999-2002). Stored serum samples (from the 1999-2002 assessment) were analyzed for activity of AChE and related enzymes. These two data sources were merged, and multiple linear regression models estimated the association of deployment, stress (anxiety) or mood disorders, and symptoms compatible with Gulf War veterans' illnesses (GWVIs), with enzyme activity. Results: Seventy-four percent ( n = 361) of veterans had been deployed to the Gulf. At the time of evaluation, 23% ( n = 113) of participants reported anxiety and 15% ( n = 71) reported mood disorders; 49% ( n = 171 of 347 eligible veterans) had symptoms of GWVIs, and the median AChE activity was 839 units. AChE activity was similar for compared groups across all categories, including an adjusted difference of −27 units ( p = .50) for deployed versus nondeployed veterans and 87 units ( p = .13) for veterans with versus without symptoms of GWVIs. Conclusions: Neither deployment to the Gulf nor symptoms compatible with GWVIs are associated with long-term serum AChE activity.